2013
DOI: 10.1002/pi.4436
|View full text |Cite
|
Sign up to set email alerts
|

Nanoheterogeneous networks by photopolymerization of perfluoropolyethers and acrylic co-monomers

Abstract: Perfluoropolyethers (PFPEs) functionalized with acrylic and methacrylic end groups can be mixed with typical hydrogenated acrylic monomers such as hexanediol diacrylate, tripropyleneglycol diacrylate and trimethylolpropane triacrylate. Mixtures are transparent up to 1:3 weight ratios and can then be photopolymerized. Crosslinked networks are obtained, showing a complex multiphasic nanostructure: submicrometric hydrogenated nanodomains are chemically linked to the fluorinated matrix. Because of this morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…It has already been reported for crosslinked methacrylate PFPAEs with different contact angles between the air and the glass sides . Moreover, the values are in good agreement with previous values found for methacrylate PFPAEs homopolymers or crosslinked acrylates PFPAEs . By using hexadecane, the same trend was observed: an increase of the hydrogenated spacer length permitted an increase in contact angle values.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has already been reported for crosslinked methacrylate PFPAEs with different contact angles between the air and the glass sides . Moreover, the values are in good agreement with previous values found for methacrylate PFPAEs homopolymers or crosslinked acrylates PFPAEs . By using hexadecane, the same trend was observed: an increase of the hydrogenated spacer length permitted an increase in contact angle values.…”
Section: Resultssupporting
confidence: 91%
“…40,41 Moreover, the values are in good agreement with previous values found for methacrylate PFPAEs homopolymers 42 or crosslinked acrylates PFPAEs. 38,43 By using hexadecane, the same trend was observed: an increase of the hydrogenated spacer length permitted an increase in contact angle values. The omniphobic properties were then proved and the polymers can be used for water-oil repellent applications.…”
Section: Contact Angle Measurementssupporting
confidence: 57%
“…As the photopolymerization kinetics are slower in the presence of air due to the quenching of radicals by oxygen (Ligon et al, 2014), the addition of MMI seems to contrast this inhibition phenomenon. It is known that the fluorinated phase of methacrylate PFPAE with hydrogenated comonomers segregate at the air side of UV-cured films and PFPAEs are able to dissolve oxygen (Vitale et al, 2013). Thus, it was expected that the fluorinated phase from MMI would migrate toward the air side, causing a surface segregation of the fluorinated domains.…”
Section: Photocopolymerization Of Maleimidesmentioning
confidence: 99%
“…Previous studies have primarily focused on free‐radical photo‐polymerization of fluorine‐containing acrylate (or methacrylate) monomers . These monomers are relatively economical and easily transformed to achieve different properties.…”
Section: Introductionmentioning
confidence: 99%
“…All of these results demonstrated that these monomers are suitable for a wide range of practical applications such as UV coatings, UV inks, and photoresists.Previous studies have primarily focused on free-radical photopolymerization of fluorine-containing acrylate (or methacrylate) monomers. [14][15][16] These monomers are relatively economical and easily transformed to achieve different properties. However, there are some obvious problems and shortcomings associated with acrylate (or methacrylate) monomers.…”
mentioning
confidence: 99%